(3eSCdI aj GdbQBfs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3eSFdI CjVkG ai GdbQBf heG hbY ajg ef GdfRGY hHjGf GdMb GdPi Od Ydjg GdcJGH hGdSfI hGdELeGY dTjNfG Hf JjejI QVi Gddg Yfg SFd Yf QLdjf JHGMKG abGd CMOgeG GdbQBf MQa hUhJ s
(3BNQgG (B:s
(3hCbhd Cgd GdMdhd GdPjf jbhdhf HGdMdhd ai GdPGJ hGdUaGJ HGWdI hgPg GdGehQ eHShWI ai ZjQ gPG GdehVY hbO HSWfGgG ai GdhGLH GdcHjQ hGddg CYde HGdUhGH hGdMeO ddg hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B2s
(3GdfSNI HgG MhGTs
(3HdZJ ebGHdI hJUMjMGJ Ydi jO cGJHgGs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3Gdabg GdMfHdjs